2018
DOI: 10.3168/jds.2017-14076
|View full text |Cite
|
Sign up to set email alerts
|

Predicting blood β-hydroxybutyrate using milk Fourier transform infrared spectrum, milk composition, and producer-reported variables with multiple linear regression, partial least squares regression, and artificial neural network

Abstract: Prediction of postpartum hyperketonemia (HYK) using Fourier transform infrared (FTIR) spectrometry analysis could be a practical diagnostic option for farms because these data are now available from routine milk analysis during Dairy Herd Improvement testing. The objectives of this study were to (1) develop and evaluate blood β-hydroxybutyrate (BHB) prediction models using multivariate linear regression (MLR), partial least squares regression (PLS), and artificial neural network (ANN) methods and (2) evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 21 publications
8
49
1
Order By: Relevance
“…The accuracy of our MIR prediction model for serum BHB was moderate (0.48 ≤ R 2 ≤ 0.60), which was better than those reported by Belay et al (2017a) and similar to those reported by Smith et al (2016) and Pralle et al (2018). The moderate accuracy may have been in part due to the low prevalence of elevated serum BHB concentrations in our data set.…”
Section: Pls Regression Models For Predicting Serum Metabolite Concensupporting
confidence: 85%
See 2 more Smart Citations
“…The accuracy of our MIR prediction model for serum BHB was moderate (0.48 ≤ R 2 ≤ 0.60), which was better than those reported by Belay et al (2017a) and similar to those reported by Smith et al (2016) and Pralle et al (2018). The moderate accuracy may have been in part due to the low prevalence of elevated serum BHB concentrations in our data set.…”
Section: Pls Regression Models For Predicting Serum Metabolite Concensupporting
confidence: 85%
“…It follows, therefore, that these models may be useful for identifying cows with metabolic disorders based on their milk MIR spectra. Several authors have converted MIR predictions of continuous traits, such as BHB concentration, into binary traits based on metabolic profile thresholds (Gelé et al, 2015;Pralle et al, 2018). As far as we know, ours is the first report using PLS-DA models to classify animals directly using milk MIR spectral data.…”
Section: Pls-da For Classifying Animals Based On Metabolic Profile Tementioning
confidence: 95%
See 1 more Smart Citation
“…The hypothesis behind this was that cows in the good and poor groups are more likely to differ in their metabolic status, which would result in different reproductive performance (Oikonomou et al, 2008;Pryce et al, 2016). Such differences in metabolic status are expected to be captured by MIR spectra (Belay et al, 2017;Grelet et al, 2018;Pralle et al, 2018;Luke et al, 2019). The metabolic characteristics of the cows in the average group were hypothesized to be similar to those of the other 2 groups, which consequently makes them difficult to differentiate.…”
Section: Resultsmentioning
confidence: 99%
“…The KBR was ground into a powder, and then mixed with Quercus dentata Thunb leaf extract to a proportion of 100:1, respectively. After grinding on a tablet [11]. (Au query: please rewrite the mention of the tablet into the sentence or place within the paragraph where it belongs.…”
Section: The Ft-ir Analysismentioning
confidence: 99%